(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2022)
Kazakhstan faced the biggest political crisis in early January 2022 in over three decades since its independence in 1991. The crisis began with protests over rising fuel prices which turned into widespread unrest followed by the crackdown and finally returning back to normalcy. It is believed that for the Kazakh President, Kassym-Jomart Tokayev, this has been the biggest crisis during his presidency, but since he has been able to control the situation it also offers an opportunity, particularly in matters of democratic reforms in the country. The article focusses on the recent developments and challenges concerning the democratic reforms undertaken in Kazakhstan. The main aim and objective is to review the key initiatives towards democratic reforms, especially the political reforms taken by Kazakhstan both before and during the period of Tokayev’s presidency. This is so because both the founding President as well as the current President have believed that democratic reforms in the political space of Kazakhstan is indispensable if this Central Asian country has to make a move into the World’s top 30 most developed nations. The methods used in this research mainly include qualitative that helped understand diverse opinions and experiences of Kazakhstan in its democratic reforms programmes and initiatives. The article concludes that despite a series of measures aimed at implementing the democratic reforms, it is still too early to predict how the democratic reforms in the political space of Kazakhstan will take shape in the future. Key words: Political Reforms, Kazakhstan-2030” Strategy, Kazakhstan-2050, Five Institutional Reforms and 100 Concrete Steps.